Le Dictionnaire numérique de la Ferme générale : de la modélisation à la mise en ligne - Valentin De Craene; Victoria Le Fourner (Humanités Numériques)
This case study presents the Dictionnaire numérique de la Ferme générale (1664-1794), a digital dictionary of the General Farm created in the course of FermeGé, which is a project accredited by the Agence nationale de la recherche in 2021, from its conceptual modelling to its Web deployment. While the dictionary initially appeared to the group of historians writing the entries to be a simple object with an organic structure, the need to make the data available in a Web environment proved to be an essential step in structuring the information. This initial point in the dialogue between historians and engineers led us to encode the structure of the records and the named entities in TEI XML to add a semantic layer to the raw text. In the same perspective, processing the bibliography and sources systematically mentioned at the end of a record enabled these elements to be indexed for later processing. This phase gradually changed the project’s approach to the dictionary. From then on, the dictionary was no longer simply an organic work, but was gradually transformed into a hybrid object backed by a relational database. The aim of this article is to analyse the contribution of digital humanities and documentary engineering to the project.